PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BAGI UMKM GADING BERSINAR - Fitri, Euis Nessia; Kurniawati, Desi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The main goal of the company is to analyze the financial reports of Gading Bersinar MSMEs and examine the financial reports of Gading Bersinar MSMEs using a Spreadsheet. The research method employed is qualitative with data analysis based on the Miles & Huberman model. Data collection techniques involve observation and interviews. The research findings indicate that Gading Bersinar MSMEs currently do not have financial reports compliant with MSME Financial Accounting Standards (SAK EMKM). Upon inputting the data into the spreadsheet system, the financial reports become more organized. One inhibiting factor is the lack of accounting understanding among MSME practitioners.